2016
DOI: 10.1002/gps.4644
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stressful life events on cerebral white matter hyperintensity progression

Abstract: Objective Exposure to stressful events is associated both with occurrence of depression and also vascular disease. The objective of this study was to determine whether higher levels of stress exposure was related to measures of pathological brain aging, specifically white matter hyperintensity volumes, in older adults with and without depression. Methods The sample included 130 depressed and 110 never-depressed older adults aged 60 years or older enrolled in a longitudinal study at an academic medical center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…Numerous epidemiological studies have identified risk factors and protective factors for late‐life mental disorders. For example, complex interactions of genetic vulnerabilities (eg, heritability), cognitive dysfunction and coping skills, age‐related neurobiological changes, medical morbidities, and/or other stressful events (eg, bereavement and social isolation) can be risk factors for mental disorders . However, a higher educational level, better socioeconomic status, engagement of other psychosocial activities, and physical activities are often referred to as protective factors …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous epidemiological studies have identified risk factors and protective factors for late‐life mental disorders. For example, complex interactions of genetic vulnerabilities (eg, heritability), cognitive dysfunction and coping skills, age‐related neurobiological changes, medical morbidities, and/or other stressful events (eg, bereavement and social isolation) can be risk factors for mental disorders . However, a higher educational level, better socioeconomic status, engagement of other psychosocial activities, and physical activities are often referred to as protective factors …”
mentioning
confidence: 99%
“…For example, complex interactions of genetic vulnerabilities (eg, heritability), cognitive dysfunction and coping skills, age-related neurobiological changes, medical morbidities, and/or other stressful events (eg, bereavement and social isolation) can be risk factors for mental disorders. [3][4][5][6] However, a higher educational level, better socioeconomic status, engagement of other psychosocial activities, and physical activities are often referred to as protective factors. [7][8][9] Yet few studies have examined the association of adverse childhood experiences (ACEs) with mental disorders in older adults.…”
mentioning
confidence: 99%
“…It can be hypothesised that these predictors might comprise a cluster of mental-health related factors, such as loneliness, anxiety or post-traumatic stress disorder, which were not assessed in this study 38 . The importance of social networks and stressful life events on mental well-being and health in general 51 , 52 , as well as the association of social economic factors with WMH have been established 53 . It was also shown that widowhood accelerates cognitive decline in cognitively normal older adults 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Probabilistic atlases show that WMHs in normal aging are generally confined to the periventricular space and total WMH volume increases with age 26,84 . Abnormally high body mass index, diabetes, stress, and hypertension are associated with increased WMH burden 84–87 . Underlying systemic vascular risk factors are considered the driver of WMH 88,89 .…”
Section: Lesions Associated With Agingmentioning
confidence: 99%